Examining the Effectiveness of Multiple Representation (SiMaYang) Learning Model on Students’ Mathematical Conceptual Understanding: The Role of Self-Efficacy - Scholts, CJ; Agus Setyaningrum, Wulan (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effectiveness of the Multiple Representation (SiMaYang) learning model on students’ mathematical conceptual understanding and to determine the role of students’ self-efficacy in influencing differences in conceptual understanding outcomes. Methodology: This study employed a quantitative approach with a quasi-experimental method using a 2×3 factorial design. Data were collected using essay tests and Likert-scale questionnaires. Statistical analysis included Liliefors normality test, Bartlett homogeneity test, independent t-test, and two-way ANOVA with unequal cells, followed by Scheffé test using statistical software. Main Findings: Results showed that the SiMaYang learning model produced higher mathematical conceptual understanding than conventional learning. Self-efficacy significantly affected students’ conceptual understanding, where high self-efficacy students performed better than others. No interaction effect was found between learning model and self-efficacy. SiMaYang model consistently improved understanding across all self-efficacy levels, indicating independent contributions of instructional model and affective factors. Novelty/Originality of this study: This study integrates cognitive and affective aspects by simultaneously examining the effect of the SiMaYang learning model and self-efficacy within a single analytical framework. It provides a more comprehensive understanding of learning effectiveness by using factorial design analysis, offering new insights into how instructional strategies and internal beliefs independently influence mathematical conceptual understanding.